2016
DOI: 10.1371/journal.pone.0168414
|View full text |Cite
|
Sign up to set email alerts
|

Neural Signatures of the Reading-Writing Connection: Greater Involvement of Writing in Chinese Reading than English Reading

Abstract: Research on cross-linguistic comparisons of the neural correlates of reading has consistently found that the left middle frontal gyrus (MFG) is more involved in Chinese than in English. However, there is a lack of consensus on the interpretation of the language difference. Because this region has been found to be involved in writing, we hypothesize that reading Chinese characters involves this writing region to a greater degree because Chinese speakers learn to read by repeatedly writing the characters. To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 71 publications
(116 reference statements)
5
27
1
Order By: Relevance
“…The Chinese characters used by this study are more visually complex stimuli than the French words used by Planton et al (), which would lead to a difference in demand for visual–spatial processing. The visual representation of Chinese characters is more likely to be bilateral in Chinese written systems (Wu, Ho, & Chen, ), and thus the visual word regions show bilateral activation during Chinese writing (Cao & Perfetti, ; Yang et al, ; Yang et al, ). This claim warrants testing in further studies comparing brain activation patterns between Chinese and alphabetic writing systems.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese characters used by this study are more visually complex stimuli than the French words used by Planton et al (), which would lead to a difference in demand for visual–spatial processing. The visual representation of Chinese characters is more likely to be bilateral in Chinese written systems (Wu, Ho, & Chen, ), and thus the visual word regions show bilateral activation during Chinese writing (Cao & Perfetti, ; Yang et al, ; Yang et al, ). This claim warrants testing in further studies comparing brain activation patterns between Chinese and alphabetic writing systems.…”
Section: Discussionmentioning
confidence: 99%
“…Some efforts have been made to unveil the neural basis of Chinese writing. For example, Cao and Perfetti ( 2016 ) directly compared the brain activation associated with mental writing of Mandarin Chinese characters and English words in a group of native speakers of Chinese and a group of English-speaking learners of Chinese. In that study, Chinese speakers showed greater activation in the middle frontal gyrus than English speakers, favoring the hypothesis that the neural substrates of written production vary across language systems (Tan et al, 2001 , 2005a ).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese children with dyslexia have shown reduced brain activity and gray matter volume in the left middle frontal gyrus 16,30,54 . This region is also known to be crucial in the coordination of cognitive resources in working memory to establish reading-writing connection 2,21 . Chinese learners who have practiced handwriting exhibited stronger activations in the left middle frontal gyrus in comparison with those who did not 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Children are encouraged to read on electronic devices and are required to learn typewriting skills. Nevertheless, reading and writing skills are closely intertwined 1,2 . Literacy learning has become susceptible to frequent typewriting due to the popularization of electronic devices and learning platforms.…”
Section: Introductionmentioning
confidence: 99%